Solution of capital investment problems via branch and bounds method - Zainodin Haji Jubok, (Universiti Kebangsaan Malaysia, 1996)
In this paper a class of capital investment problem is considered within the context of mathematical programming. The usual and commonly used approach is presented upon the basis of the next present value criterion, and a branch and bound method is discussed for a model under extended assumptions.